Disentangling left-handed and right-handed neutrino effects in B c → τ ν ¯ τ $$ B_c→ τ {\overline{ν}}_{τ } $$ decay - Quan-Yi Hu (Journal of High Energy Physics)
Abstract Inspired by the anomalies in B → D ∗ τ ν ¯ τ $$ B→ D^{\left(* \right)}τ {\overline{ν}}_{τ } $$ decay, in this work, we carefully study the influence of the most general dimension-six effective operators involving right-handed neutrinos on the four cascade decays B c → τ → ν τ h ν ¯ τ $$ B_c→ τ \left(→ ν_{τ }h\right){\overline{ν}}_{τ } $$ (h = π, ρ) and B c → τ → ν τ ℓ ν ¯ ℓ ν ¯ τ $$ B_c→ τ \left(→ ν_{τ}\ell {\overline{ν}}_{\ell}\right){\overline{ν}}_{τ } $$ (ℓ = μ, e). We calculate for the first time the analytical results of the distributions of the differential decay rates of these cascade decays with respect to the energy of the charged particles in the final state. We select a total of 13 new physics benchmark points, among which 9 are derived from the effect of purely left-handed neutrinos, and the other 4 are from the effect of purely right-handed neutrinos. We find that the benchmark points BP4, BP6, BP11, and BP13 can significantly increase the values of these distributions while the BP3 causes a sharp decrease in these distributions. The end-point behavior of the differential distribution dΓ/dE π can be used to disentangle the effects of left-handed and right-handed neutrinos. Finally, in order to eliminate the uncertainties brought by the CKM matrix element V cb and the decay constant f B c $$ {f}_{B_c} $$ , we introduce the normalized distributions dΓ/(ΓdE a ) (a = π, ρ, μ, e), which are only sensitive to the right-handed neutrinos. We find that in each normalized distribution there exists a fixed point that is not related to any dimension-six effective operators considered in this work.